Maternal perceptions of developmental stimulation for stunted toddlers: A phenomenological study in remote Indonesian islands - Suyani, Suyani; Asniar, Asniar; Marthoenis, Marthoenis (Palembang MediRose Publisher, 2024)
Background: Developmental stimulation is a shared responsibility among family members and is essential for children to achieve age-appropriate developmental milestones. However, limited evidence exists on how mothers perceive this crucial issue, particularly those with stunted toddlers. Objective: This study aimed to explore maternal perceptions of providing developmental stimulation to stunted toddlers living on the remote islands of Indonesia and how these perceptions influence their children’s growth and development.Methods: A descriptive phenomenological design was employed, involving eight mothers of stunted toddlers residing in the unique context of the remote islands in Karimun District, Riau Islands Province, Indonesia. Data were collected using demographic data sheets, interview guides, field notes, and audio recordings. The data were analyzed using Miles and Huberman’s method.Results: Two main themes emerged: (1) child development was perceived in terms of intelligence, speech, and play; and (2) concerns regarding developmental issues. Two main themes emerged: (1) child development was perceived in terms of intelligence, speech, and play; and (2) concerns regarding developmental issues.Conclusions: The findings revealed gaps in maternal understanding of child development among mothers of stunted toddlers. It is recommended that the heads of Community Health Centers and relevant stakeholders implement early detection and intervention strategies, provide health education on child development, and enhance the capacity of village health volunteers and parents to monitor toddler development. These efforts are crucial for improving the well-being and future of stunted toddlers and should be part of a comprehensive strategy.